HGG-40. NF1 mosaicism in a CMMRD-patient with a glioblastoma. (3rd June 2022) - Guerrini-Rousseau, Lea; Cabaret, Odile; Muleris, Martine; Vidaud, Dominique; Cotteret, Sophie; Rouleau, Etienne; de Beaumais, Tiphaine Adam; Varlet, Pascale; Morscher, Raphael; Abbou, Samuel; Dufour, Christelle; Brugieres, Laurence; et al.
Abstract: Constitutional Mismatch Repair Deficiency (CMMRD) and Neurofibromatosis type 1 (NF1) are brain tumor predisposing syndromes associated with café-au-lait macules (CALM). Due to this overlap, establishing the differential diagnosis can be difficult, but remains crucial as treatments and surveillance protocols clearly differ for affected patient according to the underlying disease. We reported a girl, with a clinical diagnosis of sporadic NF1 during childhood, who presented a glioblastoma at 16 years-old. Faced with the NF1-like phenotype, diagnosis of CMMRD was suspected because tumor was ultra-hypermutated (228.67 mut/Mb), with a loss of PMS2 expression in both tumor and normal cells. Germline analyses identified a compound heterozygous pathogenic variant (PV) in the PMS2 gene, with an abnormal methylation tolerance test, that confirmed CMMRD. Moreover, a NF1 PV (20% and 9% in blood and saliva samples respectively) was identified compatible with a germline mosaicism. Patient's phenotype was atypical for CMMRD, with a voluminous neurofibroma and ephelids rather observed in NF1. CMMRD oncogenesis is not currently understood, in particular involvement of an NF1 PV, which could arise early from the ultra-hypermutated burden and might explain clinical signs, in particular CALMs. CMMRD diagnosis allowed proposing an adapted genetic counseling and surveillance for the patient and her parents according to the published guidelines due to the major impact on the patient's oncological risks and prognosis. The best strategy for surveillance of the neurofibroma is still debated due to uncertainties about its risk of degeneration with a CMMRD underlying disease. This observation raises the question of the frequency of mosaic NF1 germline PV in CMMRD-patients and the time of its postzygotic appearance in the context of a biallelic deficit of one of the MMR genes. Combination of these both CMMRD and NF1 germline PVs would be a strong argument for a combination of MEK-inhibitors with immunotherapy.